Organizational communication in Pencak Silat organizations: A scientific literature mapping based on Publish or Perish and VOSviewer - Moch. Ichdah Asyarin Hayau Lailin; Ratnaningrum Zusyana Dewi (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to map and analyze the development of scientific literature on organisational communication in Pencak Silat organizations using a bibliometric mapping approach based on a systematic literature review. Data were retrieved from the Crossref database through the Publish or Perish application using predefined keywords related to organizational communication and Pencak Silat for the period 2020–2025. The retrieved publications were analyzed using VOSviewer to identify publication trends, thematic clusters, and the intellectual structure of the research field. The findings indicate that existing studies are dominated by themes of leadership, organisational culture, and athlete performance, while research explicitly examining internal and leadership communication within Pencak Silat organizations remains limited. These results highlight important research gaps and provide directions for future organisational communication studies within the context of culturally rooted martial arts organizations.